(untitled) (Biological Sciences - PJSIR, 2020)
Fatty acid levels of two edible and medicinal species: Delonix regia and Tetrapleura tetraptera seeds flour were investigated using standard analytical techniques. Among the saturated fatty acids (SFA), palmitic acid (17.2-49.4%) had the highest concentration in both samples. Oleic acid (19.7-21.0%) was most abundant among the mono-unsaturated fatty acids (MUFA). In both samples, palmitoleic acid recorded 0.00% concentration, whilst margaric acid (0.001-0.060%), lignoceric acid (0.001-0.079%) and arachidonic acid (0.065-0.080%) were found in trace amounts. Both samples were high in total poly-unsaturated fatty acids (PUFA) (26.9-42.7%). MUFA/SFA was less than 1.00 in both samples (0.375-0.584); PUFA/SFA was 1.18 (Delonix regia) and 0.507 (Tetrapleura tetraptera). Total unsaturated fatty acid (TUFA) (63.8%) was higher than total SFA(36.1%) in Delonix regia. In Tetrapleura tetraptera, SFA (53.1%) was more than TUFA (46.8%). 2n-6/3n-3 were high at 59.9 (Delonix regia) and 536 (Tetrapleura tetraptera). The correlation coefficient of the fatty acids was positively high and significant